Investigation of Saturn's aurora by whistler mode waves - Kumari J.; Tripathi A.K.; Singhal R.P.; Singh O.N., II (My University, 2025)
Saturn's aurora has been studied at relatively lower latitudes mapping to closed field lines near the open closed field line boundary. Precipitation of electrons into the atmosphere of Saturn from resonant wave-particle interaction by whistler mode waves has been considered. Precipitation flux and UV intensities of four excitations: H Lyman-α from atomic H, H Lyman-α from dissociative excitation of molecular H2, Lyman and Werner bands of H2 have been estimated. In this study observed whistler mode wave data and observed electron distribution function have been used. Calculations have been performed for the range 4.5–7.5 of L-shells. In the sub range of L-shells 5.5–7.5, the calculated UV intensities are: 0.8 R, 120−134 R, 594−664 R and 631−706 R for H Lyman-α from atomic H, H Lyman-α from molecular H2, Lyman and Werner bands of H2 respectively. The UV intensities are found negligibly small for the range of L-shells 4.5–5.5. It is estimated that higher UV intensities would be expected for whistler mode upper band chorus waves. However, these waves are less frequent in the magnetosphere of Saturn and sufficient wave data is not available to calculate the auroral emissions. © 2018